Scaling Gender Issues in Modern Muslim Societies - Abdullah, Razia; Dar, Showkat Hussain (Journal of Modern Islamic Studies and Civilization, 2026)
Gender justice has become an increasingly significant axis of inquiry within contemporary Muslim societies, where debates on women’s rights unfold at the intersection of tradition, reform, and modern statehood. This study investigates how gender inequality is produced, sustained, and scaled across legal, social, and political domains within these contexts. The paper argues that contemporary gender disparities stem not from Islamic foundational texts but from the authoritative preservation of pre-modern jurisprudential models, particularly within Personal Status Laws governing marriage, divorce, guardianship, and inheritance. These legal frameworks continue to constitute the most resilient institutional barriers to equality, with reform trajectories contingent upon political will, civil society mobilisation, and the contestation of interpretive authority. Drawing on feminist hermeneutics, reformist Islamic scholarship, and socioeconomic data, the study demonstrates that advancing gender justice requires the integration of ethical reinterpretation with legal and socio-cultural transformation. The analysis concludes that meaningful and scalable progress is attainable only through the convergence of intellectual, institutional, and grassroots efforts committed to an egalitarian rearticulation of Islamic and social norms.